A Christmas memory [large type] - Evans, Richard Paul (Thorndike Press, a part of Gale, a Cengage Company, 2022)
"It's 1967, and for young Richard it's a time of heartbreak and turmoil. Over the span of a few months, his brother, Mark, is killed in Vietnam; his father loses his job and moves the family to Utah; and his parents separate. When Richard is run down by bullies at his new school, he meets Mr. Foster, an elderly neighbor who chases off the bullies. Richard becomes fast friends with the man who inspires Richard's love for books and whose dog becomes his closest companion. With Mr. Foster's wisdom and kindness, Richard learns what truly matters: that forgiveness can heal the deepest wounds, and love endures long after the pain of loss subsides"--